The Effect of Educational Infrastructure Management on Improving the Quality of Learning Services - Siti Nurlaelah; Supiana; Ahmed Čolić (International Journal of Advanced Studies in Educational Management (IJASEM), 2025)
This research aims to determine the influence of facilities and infrastructure management on learning services at the Darul Muttaqin Foundation, Tangerang City. This research uses a quantitative approach, with research methods namely descriptive statistical methods. The data collection technique used was using questionnaires with a sample size of 87 students. The data analysis technique in this research uses instrument testing, inferential statistical analysis, assumption analysis, and hypothesis testing. Based on the research results, it shows that there is a positive and significant influence of facilities and infrastructure management on learning services at the Darul Muttaqin Foundation, Tangerang City, with a significant value of 0.000 < 0.05 and a calculated t value of 8,614 > table 1,663, so that (Ho) is rejected and (Ha) accepted. Furthermore, the coefficient of determination (R square) is 0.466, meaning that the amount of influence exerted by the management of facilities and infrastructure and learning services at the Darul Muttaqin Foundation, Tangerang City is 46.6%.